Produção do espaço urbano em Fortaleza: conflitos entre os instrumentos de valorização imobiliária e os de inclusão social no grande Mucuripe - Anjos, José Wesley Silva dos (2023)
The theme of urban space is vast when thinking about the internal and external processes of space production, as one of the main devices to understand the logic of financial capital in the metropolises of dependent capitalism. Based on this premise, the objective of this dissertation is to understand the conflicts within the regulation and application of urban instruments, within municipal management, by intensifying some urban instruments, in contrast, the slowness of others, especially when one imagines the size of the target audience that these instruments can serve in Fortaleza. Having as a temporal clipping from the Master Plan of Fortaleza in 2009 and as a spatial clipping the Great Mucuripe. Among the specific objectives we have: To analyze the dynamics of planning, its recent updates and how these planning practices seem to order or direct different actions and in which agents the planning approaches and distances itself; Understand the logic of instrumentalization in municipal politics, how these instruments are applied, in what measures they are approved and how they are stipulated within the municipal administration; Understand the movements and conflicts between the regulation of instruments in an area of the city (Grande Mucuripe) and the intentions and dealings that space production agents articulate to achieve their objectives within urban policy. The methodological research was attached to the reading of reality, based on the analysis of the processes of regulation and application of urban instruments, understanding the different geographic scales covered by the object of study and based on the reading of space, as a locus of reproduction of society and social reality. This development took place through readings with the bibliographic review of themes such as: financialization, space production, urban instruments, urban planning and strategic planning. For the documentary research, collections from public bodies such as SEUMA and IPLANFOR were used, as they work with these instruments and their application processes, analysis of forms, functions, structures and processes of this instrumentalization of space and empirical reading of the field, in addition to making cartographic data.